Être ou ne pas être (une minorité) ?Le kachoube en Pologne - Michael Hornsby; Tomasz Wicherkiewicz (Droit et Cultures, 2012)
When Poland signed the European Charter for Regional or Minority Languages on February 12th, 2009, of the fifteen languages listed all but one were categorised as minority languages. Kashubian was (apparently) the only regional language. Of course, the original wording of the Charter, when it was first drawn up in 1992, did not specify what the difference between a minority and a regional language actually was. Thus Poland's ratification, while totally complying with the Charter's original remit, is nevertheless controversial in its application of the Charter's principles. In this paper, we aim to explore the tensions that have been created by the implementation of the Charter in Poland. The most obvious point of friction concerns the singling out of Kashubian to the detriment of other less widely-used languages and this will be discussed in the context of one presenter's expert knowledge and close association with the Charter's implementation in Poland. Less obvious, but equally important, is the identification of the conflicting language ideologies at play here. If all minority languages in Poland (apart from Kashubian) are located within the confines of a «language-and-identity» ideology, then locating Kashubian within a framework of territoriality (or a `language-and-territory' ideology Myhill 1999]) is not only bound to lead to a clash of counter-productive ideologies, but also seems achronistic at a time in the history of Kashubian when it is spoken regularly by more than 50 per cent of the population in only three districts of the traditional Kashubian-speaking area. Given these conditions, we address the question of the effectiveness of such language planning for Kashubian in the final section of our paper.